Information technology and its importance in modern teaching methods - Ilyassova, B.I.; Zarkenova, L.S.; Alshinbekova, G.K. (KSU Publ., 2018)
The article explains the concept of «informatization». One of the priority directions of informatization of the society is the process of informatization of education, which involves the use of information technologies, methods and means of informatics to implement the ideas of developing education. Multimedia technology is considered, which has special didactic capabilities. The application of multimedia technology in the educational process is shown, which significantly increases the motivation and interest of students, as well as the level of mastering the necessary knowledge and skills. The definition of the term «information technology of training (ITO)» is proposed in the modern understanding as a pedagogical technology using special methods, software and hardware (cinema, audio and video facilities, computers, telecommunication networks) to work with information. The authors pay special attention to one of the main points-the importance of information technologies for teaching as an application of information technologies for creating new opportunities for transferring knowledge (teacher's activity), perception of knowledge (learner's activity), assessing the quality of instruction and, of course, educational process. The main goal of the informatization of education is identified, which consists in preparing the trainees for full and effective participation in the everyday, social and professional life activities in the information society.
Заманауи оқыту əдістемесіндегі ақпараттық технологиялар жəне олардың маңызы
Информационные технологии и их значение в современной методике обучения
Keywords: informatization; information technologies; information space; communication technologies; education modernization; software; multimedia technologies; multimedia; multimedia presentations; multimedia lessons